1976
DOI: 10.3382/ps.0551046
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Value of Five Calcium Sources for Laying Hens

Abstract: 1961. Analysis of carotenoids in corn grain. J. Agric. Fd. Chem. 9: 132-135. Reiser, R., 1950. The metabolism of polyunsaturated fatty acids in growing chicks. J. Nutr. 42: 325-336. Salmon, R. E., and J. B. O'Neil, 1973a. The effect of the level and source and a change of source of dietary fat on the fatty acid composition of the depot fat and the thigh and breast meat of turkeys as related to age. Poultry Sci. 52: 302-314.ABSTRACT Supplemental calcium sources for Red x Rock sex-linked females were studied. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 6 publications
0
13
1
Order By: Relevance
“…In the former experiment, the strain of hen used was known to produce eggs of good shell quality, whereas, the strain used in the latter experienced shell quality problems especially toward the end of the laying cycle. Both Miller and Sunde (1975) and Muir et al (1976) found that particulate size had little effect on egg shell quality. Roland et al (1974), Muir et al (1975), and Roland (1981) concluded that particulate size had no effect on shell quality if the diet contained sufficient calcium to allow the hens to consume a minimum of 3.75 g calcium per day for young birds and 4.75 g/day for older hens.…”
Section: Introductionmentioning
confidence: 95%
“…In the former experiment, the strain of hen used was known to produce eggs of good shell quality, whereas, the strain used in the latter experienced shell quality problems especially toward the end of the laying cycle. Both Miller and Sunde (1975) and Muir et al (1976) found that particulate size had little effect on egg shell quality. Roland et al (1974), Muir et al (1975), and Roland (1981) concluded that particulate size had no effect on shell quality if the diet contained sufficient calcium to allow the hens to consume a minimum of 3.75 g calcium per day for young birds and 4.75 g/day for older hens.…”
Section: Introductionmentioning
confidence: 95%
“…This hypothesis has been used to explain the improvement in eggshell quality when oyster shell replaces finely ground limestone (Scott et al, 1971). However, Muir et al (1976) and concluded that particle size had no effect on shell quality if the diet contained sufficient Ca. Mongin (1978) reported that two hydrogen ions are generated for each molecule of CaC0 3 synthesized in the shell gland, resulting in an acidosis increase until the 22nd hr after ovulation (Mongin, 1970).…”
Section: Introductionmentioning
confidence: 97%
“…Muir et al (1976) conducted an experiment using aragonite and concluded there were no significant differences among aragonite, limestone, or oyster shell in egg weight or egg shell thickness.…”
Section: Introductionmentioning
confidence: 98%